Improvement of performances HfO2-based RRAM from elementary cell to 16 kb demonstrator by introduction of thin layer of Al2O3. (November 2016) - Azzaz, M.; Benoist, A.; Vianello, E.; Garbin, D.; Jalaguier, E.; Cagli, C.; Charpin, C.; Bernasconi, S.; Jeannot, S.; Dewolf, T.; Audoit, G.; Guedj, C.; et al.
Abstract: In this article, the reliability of HfO2 -based RRAM devices integrated in an advanced 28 nm CMOS 16 kbit demonstrator is presented. In order to improve the memory performance, a thin Al2 O3 layer is inserted in the HfO2 -based memory stack (TiN/Ti/HfO2 /Al2 O3 /TiN). Thanks to extensive electrical characterizations on both single layer HfO2 and bilayer HfO2 /Al2 O3 memory stacks at device and array levels, the potential of the bilayer is put forward. From the experimental results, the thin Al2 O3 layer has allowed to improve the endurance (memory window of about one decade after 1 M cycles) and data retention (both the low and the high resistance states are stable after 6 h at 200 °C). Finally, thanks to our 3D model based on calculation of the Conductive Filament resistance using trap assisted tunneling (TAT) the role of Al2 O3 as series resistance is highlighted.